Detection of Candidate Genes Associated with Fecundity through Genome-Wide Selection Signatures of Katahdin Ewes - Reyna Sánchez-Ramos; Mitzilin Zuleica Trujano-Chavez; Jaime Gallegos-Sánchez; Carlos Miguel Becerril-Pérez; Said Cadena-Villegas; César Cortez-Romero (Animals, 2023)
One of the strategies to genetically improve reproductive traits, despite their low inheritability, has been the identification of candidate genes. Therefore, the objective of this study was to detect candidate genes associated with fecundity through the fixation index (FST) and runs of homozygosity (ROH) of selection signatures in Katahdin ewes. Productive and reproductive records from three years were used and the genotypes (OvineSNP50K) of 48 Katahdin ewes. Two groups of ewes were identified to carry out the genetic comparison: with high fecundity (1.3 ± 0.03) and with low fecundity (1.1 ± 0.06). This study shows for the first time evidence of the influence of the CNOT11, GLUD1, GRID1, MAPK8, and CCL28 genes in the fecundity of Katahdin ewes; in addition, new candidate genes were detected for fecundity that were not reported previously in ewes but that were detected for other species: ANK2 (sow), ARHGAP22 (cow and buffalo cow), GHITM (cow), HERC6 (cow), DPF2 (cow), and TRNAC-GCA (buffalo cow, bull). These new candidate genes in ewes seem to have a high expression in reproduction. Therefore, future studies are needed focused on describing the physiological basis of changes in the reproductive behavior influenced by these genes.